2016
DOI: 10.2147/ott.s100447
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade nasopharyngeal papillary adenocarcinoma: a case report and review of the literature

Abstract: Low-grade nasopharyngeal papillary adenocarcinoma is an extremely rare tumor, with only a limited number of cases reported in the literature. Some published studies have paid more attention to the clinicopathological features of nasopharyngeal adenocarcinoma, while little effort has been made to study the optimal therapeutic strategies. We report about a woman diagnosed with low-grade nasopharyngeal papillary adenocarcinoma. She received the treatment approach that combined transnasal endoscopic surgery to rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Wang et al (28) used photodynamic therapy as a postoperative adjuvant therapy for an incompletely resected primary nasopharyngeal papillary adenocarcinoma and achieved 5-year disease-free survival. In other reports, adjuvant radiotherapy was performed, and no patients developed recurrent disease or distant metastasis (4,30). These LGNPPAs were negative for TTF-1, or TTF-1 expression was not investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Wang et al (28) used photodynamic therapy as a postoperative adjuvant therapy for an incompletely resected primary nasopharyngeal papillary adenocarcinoma and achieved 5-year disease-free survival. In other reports, adjuvant radiotherapy was performed, and no patients developed recurrent disease or distant metastasis (4,30). These LGNPPAs were negative for TTF-1, or TTF-1 expression was not investigated.…”
Section: Discussionmentioning
confidence: 86%
“…12 Negativity for TG, CK20, CD15, S-100, P40, P63, CK5/6, CDX-2, prostate-specific antigen, and glial fibrillary acidic protein, and positivity for CK7, CK19, vimentin, and EMA on immunohistochemistry were reported to support the diagnosis of TL-LGNPPA in some studies. 3,5,12 Huang et al reported that S-100 was focally positive at a moderate intensity, especially in the glandular structures in three patients, but was negative in two patients. 6 In our study, immunohistochemical analysis showed that tumor cells were uniformly positive for CK7, Vim, EMA, CKpan, and TTF-1, and negative for TG, which supported the diagnoses of TL-LGNPPA.…”
Section: Discussionmentioning
confidence: 97%
“…However, a close relationship between LGNPPA and Epstein-Barr virus has not been confirmed. 5 Negative reactivity for Epstein-Barr virus encoded RNA (EBER) 3,4,6,7,9,17,18 and latent membrane protein (LMP1) 9 tumor cells was reported using in situ hybridization. KRAS, NRAS, and BRAF (V600E) gene mutations were not found in most previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no evidence of recurrence after 4 months of surgery, and further follow-up is being carried out. [ 23 ] However, the role of adjuvant radiotherapy is not established as these well-differentiated tumors respond poorly to radiation. [ 6 ] In our case, because the surgical margin was negative, and the patient was young, he did not receive adjuvant radiation therapy or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%